Multi and Single-Period Uncertain Set Covering Location Problems with Robust Optimization Approach - Rezvani, Samaneh; Moeen Moghadas, Foroogh; Dadi, Zohreh (Annals of Optimization With Applications, 2025)
In recent years, covering location problems, owing to their numerous applications, have attracted  significant attention. Since to the presence of uncertainty in real world data, in this paper a Single-Period Set Covering Location Problem (SPSCLP) as well as a Multi-Period Set Covering Location Problem (MPSCLP) under uncertainty in fixed establishment cost parameter are discussed by robust optimization approach. Various  robust optimization approaches such as box approach, ellipsoidal approach and conservatism by adjustment approach are developed to this end. The robust counterparts of  SPSCLP and MPSCLP are presented and then OR-Library dataset are  used to analyze the models.